Investigating the Effect of Games on the Learning Experience in the Science Classroom - Hinkson, Clodagh (TARA, 2021)
A systematic literature review investigating what effect games have on student engagement levels, and also what impact games have on the achievement of learning outcomes, particularly in science.
Journal article
Keywords: Gamification; Game-based Learning; Science Classroom; Secondary Education; Education, Secondary; Science--Study and teaching; Gamification